2012
DOI: 10.3844/jmssp.2012.348.360
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Tourist Arrivals Using Time Series Analysis: Evidence From Australia

Abstract: Australian tourism has a logistic trend as Butler's model shows. The stagnation has not been reached so opportunities exist to increase tourism. The logistic model predicts 7.2 million tourists in 2015 but time series models of ARIMA and VAR improve the prediction and explain the data. The ARIMA (2, 2, 2) fits well while the VAR lead to Granger causalities between the three data sets. A regression model (R 2 = 0.99) using Australian tourist arrival as a function of Europe and World arrivals allowed to further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Studies by [2] were based on forecasting tourist arrival in Kenya using statistical time series modeling techniques. 1,4) and VAR method predicted 15700656.00 million and 15985416.00 million in 2010 respectively. It was also concluded that the Thailand government tourism sector and private tourism industry sector should prepare adequately for a much more increase in number of international tourism arrival to Thailand during 2006-2010.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies by [2] were based on forecasting tourist arrival in Kenya using statistical time series modeling techniques. 1,4) and VAR method predicted 15700656.00 million and 15985416.00 million in 2010 respectively. It was also concluded that the Thailand government tourism sector and private tourism industry sector should prepare adequately for a much more increase in number of international tourism arrival to Thailand during 2006-2010.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The study of [7] used a number of time series models of tourist arrivals and ARIMA (2, 2, 2) model was the best fit than logistic model. The models were ca-…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gurudeo et al (2012),Petrevska (2012),Borhan and Arsad (2014), Yilmaz (2015), Priyangika et al (2016), Kumar and Sharma (2016), Yu et al (2017), Theara and Chukiat (2017), Chandra and Kumari (2018), Zahedjahromi (2018), Makoni and Chikobvu (2018a), Makoni et al (2018), Msofe and Mbago (2019), Tharu (2019), Makoni and Chikobvu (2021) as well as Makoni et al (2021)) used the ARIMA approach, either exclusively or alongside other forecasting models in analyzing international tourism.…”
mentioning
confidence: 99%